A formação de professores para o pleno exercício da cidadania - Christiano, Mariana Aparecida (2016)
This research has qualitative character and has the intention to analyze the importance of teacher training that addresses the principles of citizenship and social and political participation. For this, was made a survey of teachers and graduating students of an undergraduate degree in Pedagogy from a Higher Education Institution was held (HEI) of the Federal District. In order to confirm the relevance of the study, it was conducted a historical building multiple concept of citizenship throughout the history of mankind and, more specifically, in our country. In addition, we sought to identify the presence or absence of the concepts of citizenship and participation in public policies and guiding documents for the Brazilian education and teacher training, in order to realize the importance given to the subject. As instruments to survey the empirical data were made documentary analysis, for the Pedagogical Political Project Course (PPPC), as well as semi-structured interviews with five teachers and five students of the 8th semester. The analyzes from the principles of discourse analysis have emerged an understanding of citizenship as exercise of rights and duties, such as social responsibility and as an exercise of the citizen role in everyday actions. Moreover, it appears that even considers it essential that the principles of citizenship are present in teacher education, respondents point individual initiatives of teachers, and concerned to note that there is not, by the IES, a systematization of this work, in addition to the PPPC not look objectively how this work should happen. Even so, it is evident that students and teachers believe they can overcome the challenges inherent in the work of the teacher, as the pedagogical work is based on postures based on ethics, solidarity and citizenship.